"Late" manifestations of cardiovascular syphilis occurring in a young man. Issue 4 (October 1987) - Brown, A P; Dawkins, K D; Parker, D J
Abstract : A young man who presented with a short history of angina was found to have syphilitic coronary ostial stenosis six years after the primary infection. He was successfully treated with bilateral internal mammary grafts.